Perceptual image processing algorithm benchmarking - Nur Shabrina Rusli. (2012)
Since the Human Visual System (HVS) is the ultimate receiver and appreciator of natural scenes, many visual attention models have been developed and applied to various image processing applications in the past decade.In order to provide the insight for effective deployment in this project, we study various existing saliency detection models and different image processing techniques. The performance of the respective experiments is analyzed. Benchmarking the state-of-the-art technology is then made in the related area.